State of art; the use of eichhornia crassipes in the industrial wastewater phytoremediation (Revista Cientifica Ingenio Magno, 2019)
Industrial wastewater requires control and management of its current production, according to existing literature, it is necessary that these are subjected to a quality treatment that works for continuous use and utilization, where it is also made an effective use of the water hyacinth floating macrofita (Eichhornia crassipes), which provides a treatment of industrial wastewater, obtaining high productivity and high efficiency of nutrient removal. This article aims to analyze the literature researched on macrophyte water hyacinth, involving, environmental sustainabili-ty, general aspects, background, design models, advantages and disadvantages, remediation, phytoremediation mechanism and current industrial wastewater treatment in the application of this phytoremediator method.
Keywords: eichhornia crassipes; Phytoremediation; Floating Macrophyte; Removal of Pollu-tants; Water Resources; Wastewater Treatment